If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -8 = 8 + -12 Reorder the terms: -8 + 4x = 8 + -12 Combine like terms: 8 + -12 = -4 -8 + 4x = -4 Solving -8 + 4x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 4x = -4 + 8 Combine like terms: -8 + 8 = 0 0 + 4x = -4 + 8 4x = -4 + 8 Combine like terms: -4 + 8 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| a^2=(2-a^3)-a(2a-a^4) | | 2=1/3y=1 | | 4n-5=3x+2 | | 19=-5x-3(-5x+17) | | 5x-30=-x-30 | | 10+7=18 | | (r-3t)=2 | | X-85=2/4 | | (6x)+(4x)=180 | | X=y^2-2y+5 | | 7x-bx=-28 | | -7x+12=-30 | | -0.4(6-x)-5(y+0.3)= | | 2/3:19/29::8/7? | | 9+(6x-9)-8= | | 9(m+4)-9m-36= | | 3x+2x=3y | | 4(m+9)-4m-36= | | -41=-6+7(1+6b) | | -(6s+4)-(s+5)= | | -3x^6y^4/x^-3y^-2= | | 5v+1=-89 | | 3x-18=204 | | 18v=360 | | (2x-3)(5x+6)=0 | | 31=x+20 | | K+11=12 | | 5p=80 | | 2.67+5.67X+X^2=0 | | 2.67+5.67+X^2=0 | | 3q^2-44q+130=0 | | 13=a-3.5 |